GenBank. Issue Volume 49:Issue D1(2021) (16th November 2020) - Sayers, Eric W; Cavanaugh, Mark; Clark, Karen; Pruitt, Kim D; Schoch, Conrad L; Sherry, Stephen T; Karsch-Mizrachi, Ilene
Abstract: GenBank ® (https://www.ncbi.nlm.nih.gov/genbank/ ) is a comprehensive, public database that contains 9.9 trillion base pairs from over 2.1 billion nucleotide sequences for 478 000 formally described species. Daily data exchange with the European Nucleotide Archive and the DNA Data Bank of Japan ensures worldwide coverage. Recent updates include new resources for data from the SARS-CoV-2 virus, updates to the NCBI Submission Portal and associated submission wizards for dengue and SARS-CoV-2 viruses, new taxonomy queries for viruses and prokaryotes, and simplified submission processes for EST and GSS sequences.